2015
DOI: 10.1002/admi.201500195
|View full text |Cite
|
Sign up to set email alerts
|

Silver Iodide Formation in Methyl Ammonium Lead Iodide Perovskite Solar Cells with Silver Top Electrodes

Abstract: Silver is a low‐cost candidate electrode material for perovskite solar cells. However, in such cells the silver electrodes turn yellow within days of device fabrication. The color change is also accompanied by a dramatic decrease in the power conversion efficiency when compared to otherwise identical devices using gold electrodes. Here, it is shown that the color change results from silver oxidation to silver iodide, due to a reaction with iodine in methyl ammonium lead perovskite. The change in X‐ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
603
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(635 citation statements)
references
References 60 publications
31
603
1
Order By: Relevance
“…While the loss of V oc was relatively lower, the increased degradation may come from the fact that iodine can migrate through HTL reacting with Ag and altering the electronic properties of the Ag/HTL interface. 23,27 A similar phenomenon has been also shown for Al-contacted devices. 27 This further confirms that metal electrodes (Au 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 and Ag) are intrinsically incompatible with organic Spiro-MeOTAD HTL-based perovskite devices such as solar cells [41][42][43] , photodetectors [44][45][46] , lasers 47 Figure S8).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…While the loss of V oc was relatively lower, the increased degradation may come from the fact that iodine can migrate through HTL reacting with Ag and altering the electronic properties of the Ag/HTL interface. 23,27 A similar phenomenon has been also shown for Al-contacted devices. 27 This further confirms that metal electrodes (Au 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 and Ag) are intrinsically incompatible with organic Spiro-MeOTAD HTL-based perovskite devices such as solar cells [41][42][43] , photodetectors [44][45][46] , lasers 47 Figure S8).…”
supporting
confidence: 74%
“…6, [14][15][16][17][18] Interestingly, in addition to the perovskite-related degradation, the stability of the devices was found to greatly depend on device architecture. 17,[19][20][21][22][23][24] This was explained partly by interfacial degradation 19,25 and also by degradation of the charge transporting layers. 14,22 Recently, there have been efforts to substitute the widely-used organic Spiro-MeOTAD hole transporting layer (HTL) with inorganic materials to improve the stability of PSCs.…”
mentioning
confidence: 99%
“…Instead of Debye capacitances, the interface polarization is dominated by the complex interaction between electronic and ionic species at both sides of the contact. 27,28 Our experiments can then be considered as examples of the response of non-reacting contacts.…”
mentioning
confidence: 99%
“…[87] As seen in Figure 12a-c, TEM images showed nodule-shaped AgNWs and EDX data indicated the formation of I-based compounds. Kato et al suggested as a plausible mechanism that the CH 3 NH 3 PbI 3 layer first decomposes into mobile I sources, such as CH 3 NH 3 I and HI, with the presence of water or oxygen in ambient conditions [149] ( Figure 12d). These I sources then migrate through pinholes, which are known to be formed in Spiro-OMeTAD layers, with an average diameter of ≈135 nm and a surface density of ≈3.72 holes/µm 2 .…”
Section: Top Menw-network Electrodesmentioning
confidence: 99%